Tinjauan Hukum Ekonomi Islam Tentang Praktik Jual Beli Buket Bunga Uang (Studi Kasus Di Kios Balonku Party And Event Organizer Garut) - Wati, Ai; Haq, Husni Muhammad Hufadzul (Jurnal Hukum Ekonomi Syariah, 2023)
This thesis is the result of research on my balloon kiosk where one of the items being sold is a bouquet of money which is real money put in the form of a bouquet which in the end the buyer gives a fee to the seller. This researcher examines the ijarah contract for a bouquet of money with money, where in the transaction here the source is wages for giving money with money, where the seller sells money in the form of a bouquet of money and the buyer receives more money in the form of a bouquet, which is the money in the bouquet can be reused by the buyer as a medium of exchange. If viewed from a religious point of view, the money-bouquet business at my balloon kiosk prohibits excessive fees for services. The problem in this research is how the practice of the ijarah contract for the bouquet of money that occurs at my balloon kiosk and what is the view of Islamic law regarding the ijarah contract for the bouquet of money at my balloon kiosk. This study aims to determine the practice of the ijarah bouquet contract that occurs at the Balonkudan kiosk to find out the views of Islamic law on the ijarah bouquet of money contract at the Balonku kiosk. This type of research is field research using primary data and secondary data. Sources of data in research using observation and interview methods. While the data analysis is descriptive qualitative by using an inductive mindset. The findings or results of this study can be stated that the practice of the ijarah contract for a bouquet of money at the Balonku kiosk is in practice carried out by ordering the product in advance, payment is made at the beginning of the job when ordering the product. Then when the bouquet of money is ready, the seller suggests that the buyer take it himself, because the seller does not want to take the risk if the item is taken away by an irresponsible person. The practice of the ijarah contract for money bouquets that took place at my balloon kiosk is valid, because the fee for this money bouquet service is not more than the money to be made into the bouquet. So the payment of wages to the seller must not exceed the price of the bouquet of money and there must be a consent qabul at the place where the transaction took place before it changed hands. Wages are essentially permissible in Islamic law and must be obeyed and must not violate existing regulations. Keywords – Information Systems, Islamic Boarding Schools, SDLC